(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The main purpose of this paper is to construct an optimal portfolio by applying Sharpe’s single-index model. The present study is based on the secondary data. For the purpose of constructing an optimal portfolio, a sample of top fifteen stocks listed on Bombay Stock Exchange (BSE) was selected in this study. BSE Sensitive Index (Sensex) has been used as market index. Monthly closing prices of selected stocks as well as market index for the period of April 2011 to March 2017 were used in this study. A unique cut off point was computed. The results of the study have been constructed an optimal portfolio. The findings of the study will be useful for investors and practically related for the purpose of investing.